THE INTERNATIONAL STUDENTS PERCEPTION ABOUT HOSPITALITY PRACTICES AT FEDERAL UNIVERSITY OF MARANHÃO (BRASIL): HOSPITALITY PRACTICES AT FEDERAL UNIVERSITY OF MARANHÃO: ANALYSIS OF INTERNATIONAL STUDENTS PERCEPTION OF WELL RECEIVING (Revista Contexto & Educação, 2022)
The well-received has been translated and evidenced strongly in large organizations, to include the public universities, since the valorization of the relations through practices of hospitality has been one of the main means of welcoming to the foreign students. In view of the above, this article aims to understand the perception of foreign students, participants in the Program for Alliances for Education and Training (PAEC) and the Program of Students-Agreement for Graduation (PEC-G), which study at the Federal University of Maranhão (UFMA), Campus Dom Delgado, São Luís, about the hospitality practices promoted by this institution. The qualitative research is based on the case study. For data collection, the questionnaire was used, applied with 20 students through the use of the free tool called Google Forms. The results indicate that the majority of the students are participants in the PEC-G, coming from countries that are part of the African continent and Latin America, with the largest influx of students in the semester of 2018.1 In addition, the students point out that there is a long way in UFMA for the development of more solid hospitality practices with foreign students.
Keywords: Students. Hospitality. Internationalization. UFMA